(untitled) (Texas Journal of Medical Science, 2026)
Dental caries remains one of the most common dental pathologies worldwide. Despite the development of preventive measures and improved treatment methods, the prevalence of the disease remains high among various age groups. Modern therapeutic dentistry focuses not only on eliminating defects in hard dental tissues but also on early diagnosis, minimally invasive treatment, and recurrence prevention. This article discusses modern methods of diagnosis, treatment, and prevention of dental caries